Comparative Evaluation of Alginate-Gelatin Hydrogel, Cryogel, and Aerogel Beads as a Tissue Scaffold - Ece Bayır (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Hydrogels are frequently used in tissue engineering and regenerative medicine, drug delivery, and environmental remediation. Alginate and gelatin, which are frequently used natural polymers to form hydrogels, were chosen in this study to form a core-shell structured hydrogel. Cryogels and aerogels were obtained by drying hydrogels with different methods, freeze-drying, and the continuous flow of supercritical CO2, respectively. The potential use of hydrogels, aerogels, and cryogels as a tissue scaffold was evaluated comparatively. Characterizations of materials were determined morphologically by scanning electron microscope and computed-micro tomography, chemically by energy dispersive spectroscopy, and mechanically by the dynamic mechanical analyzer. In addition, the cytotoxic effect of all structures was analyzed by the WST-1 method and the localization of the cells in these structures was determined by microscopic methods. All scaffolds show non-cytotoxic effects. Cryogels have the highest porosity (85.21 %) and mean pore size values (62.3±26.8 µm). Additionally, cryogels show high water retention capacity (782±53.5%) than aerogels (389±2.5%) for 24 h. The elastic modulus values were